2014
DOI: 10.1002/eji.201343873
|View full text |Cite
|
Sign up to set email alerts
|

Myosin 1g regulates cytoskeleton plasticity, cell migration, exocytosis, and endocytosis in B lymphocytes

Abstract: Myosin 1g (Myo1g) is a hematopoietic-specific myosin expressed mainly by lymphocytes. Here, we report the localization of Myo1g in B-cell membrane compartments such as lipid rafts, microvilli, and membrane extensions formed during spreading. By using Myo1g-deficient mouse B cells, we detected abnormalities in the adhesion ability and chemokineinduced directed migration of these lymphocytes. We also assessed a role for Myo1g in phagocytosis and exocytosis processes, as these were also irregular in Myo1g-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 51 publications
1
48
0
10
Order By: Relevance
“…Given the comprehensive analysis of B cell subpopulations, we identified eQTL-effects on MYO1G expression and on the expression of a neighboring lncRNA. MYO1G has previously been implicated in B cell biology and blood cell numbers in a mouse model (Maravillas-Montero et al., 2014). Together, these results suggest the involvement of MYO1G in the active regulation of B cell levels in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Given the comprehensive analysis of B cell subpopulations, we identified eQTL-effects on MYO1G expression and on the expression of a neighboring lncRNA. MYO1G has previously been implicated in B cell biology and blood cell numbers in a mouse model (Maravillas-Montero et al., 2014). Together, these results suggest the involvement of MYO1G in the active regulation of B cell levels in humans.…”
Section: Discussionmentioning
confidence: 99%
“…). For example, the loss of MyoA in Dictyostelium brings a reduction in chemotaxis; a similar phenomenon has been described for Myo1g in B cells . Another example is MyoE from Dictyostelium discoideum that can bind to the same phospholipids (PIP 3 ) of the membrane than Myo1g and Myo1f from mice .…”
Section: Class I Myosinsmentioning
confidence: 56%
“…The analysis of lymphocyte proteomic profiles by mass spectrometry indicated that Myo1g is the most abundant class I myosin expressed by T lymphocytes. It localizes in the plasma membrane and is particularly enriched at the cell‐surface microvilli of T and B lymphocytes . Myo1g is also present in lipid rafts from B lymphocytes and neutrophils .…”
Section: Myosin 1g: Regulation Of Plasma Membrane Tensionmentioning
confidence: 99%
“…In contrast, it is also known that this same alteration concurrently reduces the exocytosis of GPI‐anchored proteins in HeLa cells [Gauthier et al, ]. Additionally, we have previously reported an increase in the phagocytosis of S. aureus and a reduction in the secretion of tumor necrosis factor‐α by Myo1g −/− B‐cells [Maravillas‐Montero et al, ].…”
Section: Discussionmentioning
confidence: 86%
“…To eliminate the possibility that these changes were due to differences in CXCR5 expression, WT and Myo1g −/− B‐cells were stained and analyzed by FACS. The expression of CXCR5 is similar in the B‐lymphocytes from both types of mouse [Maravillas‐Montero et al, ].…”
Section: Resultsmentioning
confidence: 99%